A novel method to create long capture volumes for video tracking - Lyu, B.; Smith, L.; Ward, J.; Kensrud, J. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
This study examined a novel method to create a long and narrow calibrated capture volume for tracking objects. The methodology relies on the reflection of parallel distance-measuring lasers. Images of a board, blocking the lasers as it is moved through the field of interest, were assembled into a virtual calibration fixture. The method accommodates large calibration volumes and can be used with multiple cameras, providing a consistent absolute positional reference that is difficult to achieve with large mechanical calibration boards. This study considered a 17.4 m long tracking volume. A 0.9 m long rod was tracked throughout the calibrated volume where its average tracked length was within 0.2% of its measured length. The speed of balls traveling through the calibrated volume were within 0.1% of independent speed sensors. The average residual error of a ball`s tracked trajectory and a polynomial fit was within 1.5 mm. The method shows promise as an efficient means of calibrating large calibration volumes with multiple camera pairs.